2000
DOI: 10.1046/j.1365-2168.2000.01437.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical relevance of sentinel lymph nodes outside the axilla in patients with breast cancer

Abstract: Sentinel lymph nodes outside level I-II of the axilla were present in 19 per cent of patients with breast cancer in this series. Biopsy of these nodes was technically demanding but was performed without additional morbidity. The clinical impact was limited; treatment changed in only 3 per cent. Presented to the 52nd annual meeting of the Society of Surgical Oncology in Orlando, Florida, USA, March 1999 and the First International Congress on the Sentinel Node in Diagnosis and Treatment of Cancer in Amsterdam, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
63
1
14

Year Published

2000
2000
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 132 publications
(80 citation statements)
references
References 30 publications
2
63
1
14
Order By: Relevance
“…These patients are described in detail separately. 13 The sentinel lymph node was identified during the operation in 126 patients (93%). A total of 224 sentinel lymph nodes was harvested, with an average of 1.7 sentinel lymph nodes per patient (range, 1-4).…”
Section: Resultsmentioning
confidence: 99%
“…These patients are described in detail separately. 13 The sentinel lymph node was identified during the operation in 126 patients (93%). A total of 224 sentinel lymph nodes was harvested, with an average of 1.7 sentinel lymph nodes per patient (range, 1-4).…”
Section: Resultsmentioning
confidence: 99%
“…Esta técnica é baseada no princípio do envolvimento progressivo dos linfonodos axilares pelas células tumorais, sendo a axila o principal local de acometimento linfonodal metastático. O LS fora da axila pode ocorrer em até 16,8% dos casos, porém o impacto clínico é limitado, modificando a conduta em apenas 3% dos casos 13 .…”
Section: Discussionunclassified
“…Em publicações baseadas em bancos de dados, a ocorrência do linfonodo IM varia de 0,6 14 a 2% 8,11 e a ocorrência do LS-IM na ordem de 0,2 10 a 2,6% 13 . Por outro lado, a prevalência desse achado na anatomia patológica é de 1 a 28% 7, 15 .…”
Section: Discussionunclassified
“…The prognostic value of IM lymph node involvement alone is similar to the value of axillary lymph node involvement (Noguchi et al, 1993;Veronesi et al, 1999). However, the importance of finding a non-axillary sentinel node will mainly be dependent on it being the only involved node which occurs in less than 10% of cases where the IM nodes are involved (Donegan, 1977;Jansen et al, 2000). A small proportion of axillary node negative patients have IM node metastases but today, we are not able to predict which patients these are.…”
mentioning
confidence: 99%
“…The lack of interest in the IM node means that many surgeons today have no experience of the procedure nor have they had to deal with the complications of the procedure such as haemo-or pneumothorax (Bembenek and Schlag, 2000). However, a few studies have shown that non-axillary sentinel node biopsy can be performed with few side effects and a relatively high success ratio (Jansen et al, 2000;Noguchi et al, 2000;Dupont et al, 2001) although this has to be confirmed in other centres and countries.…”
mentioning
confidence: 99%